The need to update and improve the regulation of cross border insolvency in Cuba - Molina Rivas, Adriana Mae (2021)
Cross-border insolvency is configured when insolvency proceedings are initiated and the debtor’s assets are located in more than one State or there are foreign creditors. As this situation of patrimonial crisis involves several jurisdictions, nations have come to sign international agreements and reinforced their internal regulations in order to establish mechanisms thatallow these conflicts to be resolved. In order to facilitate the foregoing, the United Nations Commission for the Development of International Trade Law prepared the Model Law on cross-border insolvency, whose provisions have been incorporated into the bankruptcy laws of different countries as it contains valuable rules that make possible the coordination of insolvency proceedings, the recognition of a foreign insolvency proceeding, and the access of foreign creditors and representatives to the courts of another State to participate in a process of this nature. In the case of Cuban legislation, insufficient regulation of cross-border insolvency is evident, which has a negative impact on itsresolution. As a result of this problem, the present study pursues the following objective: to establish, based on a theoretical and doctrinal analysis, the need to update and improve the aforementioned regulation in Cuba both in the field of domestic law and in conventional international law.